ON THE ISSUE OF IMPROVING THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN IN THE FIELD OF SCIENCE - Karzhaubaev Серик Сеитович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
Science, as a branch of the economy, always needs to be stimulated. The primary thing in this is to stimulate the scientists themselves, as the most important link in the development of science. Therefore, it is necessary to take steps to improve legislation in the field of science. The first direction of improving legislation is the procedure for awarding academic titles. The current practice of awarding academic titles requires revision, as it does not take into account many problems. The first such problem is the complexity of publication in national and international publications recommended by the authorized body in the field of science. The second problem is a complicated publication procedure that requires certain financial costs. In this article, the author proposes to provide clear criteria for awarding an academic title. Such conditions should be work experience as a teacher and scientific work experience of more than fifteen years in educational organizations and scientific organizations. Along with this, it is necessary to have scientific publications as an important condition for the "maturity" of a scientist. If a scientist has such achievements, it is necessary to develop a procedure for awarding scientific titles by petition of the Academic Council of a scientific or educational organization to the Ministry of Science. The second direction of improving legislation is the material remuneration of scientists. The current allowances do not meet the principle of fairness. There is a gross disproportion in material allowances, generating resentment among scientists. The author in the article proposes to change the size of surcharges based on the principle of justice and humanism, establishing a gap between the degrees of five MCI. This approach will help to avoid many social problems and improve the system of surcharges. The third direction of improving legislation is represented by the problem of the duration of annual leave for scientists. The current norms, as well as material allowances, do not meet the principle of fairness. The author proposes to provide for setting the duration of annual work leave for doctors of sciences at fifty–six calendar days, for candidates of sciences – forty-nine days, for doctors of philosophy (PhD) and doctors in the profile - forty-two calendar days.